2011
DOI: 10.1177/0960327111400109
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of buccal mucosal cells in fluorosis – A new paradigm

Abstract: Study background: Fluorosis is one of the manifestations of chronic poisoning from long-term exposure to high levels of fluoride. An estimated 62 million people in 17 states in India are affected with dental and skeletal fluorosis. Objective: To evaluate the cytological morphology of exfoliated oral mucosal cells among various stages of fluorosis patients compared with controls. Design and methods: Exfoliative cytology PAP-stained smears of 21 cases of fluorosis and 21 controls subjected to morphometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Fluoride is thought to inhibit the activity of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase, and catalase [13]. Moreover, fluoride can alter glutathione levels, often resulting in excessive production of ROS at the mitochondrial level, leading to damage to cellular components [2,32,37].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride is thought to inhibit the activity of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase, and catalase [13]. Moreover, fluoride can alter glutathione levels, often resulting in excessive production of ROS at the mitochondrial level, leading to damage to cellular components [2,32,37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, current literature about the genotoxic potential of fluoride in various cells and/or tissues is contradictory. Studies have shown that fluoride does not induce DNA damage [5355], whereas other studies have observed fluoride-induced DNA damage in rat and human cells [52,56,57]. The possible mechanisms of fluoride-induced DNA damage are that (1) fluoride directly attacks the free amine groups present in DNA or (2) fluoride acts indirectly through free radicals to create DNA adducts at hydrogen bonds [58].…”
Section: Discussionmentioning
confidence: 99%
“…Rats exposed to fluoride at 150 mg/L contributed to cell cycle disruption of oral cells as depicted by a lower cell number at G 0 /G 1 as well as mitotic cells (68). In humans, exfoliate cytology in oral mucosa cells of individuals with diagnosed fluorosis pointed out apoptosis process as demonstrated by the increased nuclear size and decreased cell size (69). Toppical application of 1.23% acidulated phosphate fluoride to oral mucosa of rabbits after 1.…”
Section: In Vivo Studiesmentioning
confidence: 98%